Islam and Shariah offences in Malaysian constitutional framework: issues and challenges - Ahmad Bustami, Tajul Aris (2018)
This paper discusses the position of Islam in the Malaysian constitution and the enforcement of laws relating to shariah offences in Malaysia. It looks at the basic governing legal provisions relating to Islam and shariah offences both at Federal and State levels. The authorities and powers provided for the syariah courts officers and judges are also analysed. This paper focuses on the legal issues surrounding the investigation, prosecuting and courts’ power in dealing with the offences. With the current state of legal provisions and infrastructures, the paper finds that there are many rooms for the improvement for the Islamic Legal system in Malaysia particularly with regard to the upgrading the status, image and jurisdiction of the syariah courts.